Functional sympatholysis in mouse skeletal muscle involves sarcoplasmic reticulum swelling in arterial smooth muscle cells. Issue 23 (1st December 2021) - van der Horst, Jennifer; Møller, Sophie; Kjeldsen, Sasha A. S.; Wojtaszewski, Jørgen F. P.; Hellsten, Ylva; Jepps, Thomas A.
Abstract: The vasoconstrictive effect of sympathetic activity is attenuated in contracting skeletal muscle (functional sympatholysis), allowing increased blood supply to the working muscle but the underlying mechanisms are incompletely understood. The purpose of this study was to examine α‐adrenergic receptor responsiveness in isolated artery segments from non‐exercised and exercised mice, using wire myography. Isometric tension recordings performed on femoral artery segments from exercised mice showed decreased α‐adrenergic receptor responsiveness compared to non‐exercised mice (logEC50 −5.2 ± 0.04 M vs. −5.7 ± 0.08 M, respectively). In contrast, mesenteric artery segments from exercised mice displayed similar α‐adrenergic receptor responses compared to non‐exercised mice. Responses to the vasoconstrictor serotonin (5‐HT) and vasodilator isoprenaline, were similar in femoral artery segments from non‐exercised and exercised mice. To study sarcoplasmic reticulum (SR) function, we examined arterial contractions induced by caffeine, which depletes SR Ca 2+ and thapsigargin, which inhibits SR Ca 2+ ‐ATPase (SERCA) and SR Ca 2+ uptake. Arterial contractions to both caffeine and thapsigargin were increased in femoral artery segment from exercised compared to non‐exercised mice. Furthermore, 3D electron microscopy imaging of the arterial wall showed SR volume/length ratio increased 157% in smooth muscle cells of the femoral artery from the exercised mice, whereas there was no difference in SR volume/length ratio in mesenteric artery segments. These results show that in arteries surrounding exercising muscle, the α‐adrenergic receptor constrictions are blunted, which can be attributed to swollen smooth muscle cell SR's, likely due to increased Ca 2+ content that is possibly reducing free intracellular Ca 2+ available for contraction. Overall, this study uncovers a previously unknown mechanism underlying functional sympatholysis. Abstract : The mechanisms blunting sympathetic vasoconstriction in exercising muscle—termed functional sympatholysis—remain incompletely understood. We have taken a completely novel approach and studied femoral artery segments isolated from the skeletal muscle in mice immediately after exercise. This study reveals a previously unknown mechanism contributing to functional sympatholysis over 90 years after the phenomenon was first described.